COVID-19 in a MS patient treated with ocrelizumab: does immunosuppression have a protective role? - Novi, Giovanni; Mikulska, Malgorzata; Briano, Federica; Toscanini, Federica; Tazza, Francesco; Uccelli, Antonio; Inglese, Matilde (Multiple sclerosis and related disorders, 2020)
•A MS patient treated with ocrelizumab healed from COVID-19 without consequences•Immunosuppression might have played favorable role•This report supports the use of immunosuppressants in serious COVID-19 c Coronavirus disease 19 (COVID-19) is a novel disease entity that is spreading throughout the world. It has been speculated that patients with comorbidities and elderly patients could be at high risk for respiratory insufficiency and death. Immunosuppression could expose infected patients to even higher risks of disease complications due to dampened immune response. However, it has been speculated that overactive immune response could drive clinical deterioration and, based on this hypothesis, several immunosuppressants are currently being tested as potential treatment for COVID-19. In this paper we report on a patient that has been treated with ocrelizumab (a B-cell depleting monoclonal antibody) for primary progressive multiple sclerosis who developed COVID-19. Despite complete B cell depletion, patient symptoms abated few days after hospitalization, and he was discharged to home-quarantine. Phone interview follow-up confirmed that, after 14 days, no new symptoms occurred. This report supports the putative role of immunosuppressive therapy in COVID-19 affected patients.